1999
DOI: 10.1111/j.1572-0241.1999.984_g.x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Upper and Lower Gastrointestinal Tract Findings in Liver Transplant Candidates Undergoing Screening Endoscopic Evaluation

Abstract: Among all the findings, only rectal varices and colopathy were of higher prevalence in the pre-liver transplant population than that reported for the general population. No significant associations were found between these gastrointestinal tract lesions and patient characteristics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
33
2
3

Year Published

2003
2003
2017
2017

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(42 citation statements)
references
References 25 publications
4
33
2
3
Order By: Relevance
“…Primignani et al [34] confirmed the correlation of PHG with severity of portal hypertension, by correlating PHG with presence and size of esophageal varices. Sacchetti et al [24] Cirrhosis 142 38 (27%) 28 (20%) 10 (7%) D'Amico et al [25] Cirrhosis 212 130 (61%) 110 (52%) 20 (9%) Calès et al [26] Cirrhosis 100 98 (98%) 57 (57%) 41 (41%) Rabinovitz et al [27] Cirrhosis 510 (43%) Not reported Not reported Iwao et al [28] Cirrhosis 47 32 (68%) 15 (32%) 17 (36%) Taranto et al [29] Cirrhosis 394 317 (80.5%) Not reported Not reported Gupta et al [30] Cirrhosis 230 (61%) (52%) (9%) Iwao et al [31] Cirrhosis 476 254 (53%) 208 (43%) 46 (9%) Carpinelli et al [32] Cirrhosis 566 362 (64%) 192 (34%) 170 (30%) Zaman et al [33] Cirrhosis 120 74 (62%) 47 (39%) 27 (23%) Primignani et al [34] Cirrhosis 373 299 (80%) 127 (34%) 172 (46%) Chaves et al [35] Cirrhosis vs schistosomiasis 43 18 (81%) vs 7 (33%) Not reported Not reported Merkel et al [36] Cirrhosis 62 49 (79%) 29 (46%) 20 (32%) Merli et al [37] Cirrhosis, with mild portal hypertension 222 48 (21%) 43 (19%) 5 (2%) Ito et al [38] Cirrhosis 47 13 (27%) 10 (21%) 3 (6%) De Palma et al [39] Cirrhosis 37 23 (62%) Not reported Not reported Menchén et al [40] Cirrhosis 549 353 (64%) 275 (50%) 77 (14%) Yüksel et al [41] Cirrhosis 114 total 76 (66%) 38 (33%) 38 (33%) Fontana et al [42] Cirrhosis or bridging fibrosis from hepatitis C 1016 374 (37%) 345 (34%) 29 (3%) Bresci et al [43] Cirrhosis 85 36 (42%) Not reported Not reported Akatsu et al [44] End stage liver disease 29 19 (65.5%) 18 (62.1%) 1 (3.4%) Zardi et al [45] Cirrhosis 266 84 (31%) Not reported Not reported Barakat et al [46] Cirrhosis with portal hypertensive duodenopathy 105 105 (100%) 17 (16.2%) 88 (83.8%) Bellis et al [47] Cirrhosis 59 44 (76%) 16 (27%) 28 (47%) Gravante et al [48] Liver transplant candidates with cirrhosis 80 41 (51.2%) Not reported Not reported Canlas et al [49] [58] Cirrhosis 611 448 (73.3%) 37.3% 36% Abbasi et al [59] Cirrhosis 102 87 (85%) Not reported Not reported Ahmed et al …”
Section: (50%) Not Reported Not Reportedmentioning
confidence: 99%
“…Primignani et al [34] confirmed the correlation of PHG with severity of portal hypertension, by correlating PHG with presence and size of esophageal varices. Sacchetti et al [24] Cirrhosis 142 38 (27%) 28 (20%) 10 (7%) D'Amico et al [25] Cirrhosis 212 130 (61%) 110 (52%) 20 (9%) Calès et al [26] Cirrhosis 100 98 (98%) 57 (57%) 41 (41%) Rabinovitz et al [27] Cirrhosis 510 (43%) Not reported Not reported Iwao et al [28] Cirrhosis 47 32 (68%) 15 (32%) 17 (36%) Taranto et al [29] Cirrhosis 394 317 (80.5%) Not reported Not reported Gupta et al [30] Cirrhosis 230 (61%) (52%) (9%) Iwao et al [31] Cirrhosis 476 254 (53%) 208 (43%) 46 (9%) Carpinelli et al [32] Cirrhosis 566 362 (64%) 192 (34%) 170 (30%) Zaman et al [33] Cirrhosis 120 74 (62%) 47 (39%) 27 (23%) Primignani et al [34] Cirrhosis 373 299 (80%) 127 (34%) 172 (46%) Chaves et al [35] Cirrhosis vs schistosomiasis 43 18 (81%) vs 7 (33%) Not reported Not reported Merkel et al [36] Cirrhosis 62 49 (79%) 29 (46%) 20 (32%) Merli et al [37] Cirrhosis, with mild portal hypertension 222 48 (21%) 43 (19%) 5 (2%) Ito et al [38] Cirrhosis 47 13 (27%) 10 (21%) 3 (6%) De Palma et al [39] Cirrhosis 37 23 (62%) Not reported Not reported Menchén et al [40] Cirrhosis 549 353 (64%) 275 (50%) 77 (14%) Yüksel et al [41] Cirrhosis 114 total 76 (66%) 38 (33%) 38 (33%) Fontana et al [42] Cirrhosis or bridging fibrosis from hepatitis C 1016 374 (37%) 345 (34%) 29 (3%) Bresci et al [43] Cirrhosis 85 36 (42%) Not reported Not reported Akatsu et al [44] End stage liver disease 29 19 (65.5%) 18 (62.1%) 1 (3.4%) Zardi et al [45] Cirrhosis 266 84 (31%) Not reported Not reported Barakat et al [46] Cirrhosis with portal hypertensive duodenopathy 105 105 (100%) 17 (16.2%) 88 (83.8%) Bellis et al [47] Cirrhosis 59 44 (76%) 16 (27%) 28 (47%) Gravante et al [48] Liver transplant candidates with cirrhosis 80 41 (51.2%) Not reported Not reported Canlas et al [49] [58] Cirrhosis 611 448 (73.3%) 37.3% 36% Abbasi et al [59] Cirrhosis 102 87 (85%) Not reported Not reported Ahmed et al …”
Section: (50%) Not Reported Not Reportedmentioning
confidence: 99%
“…A major cause of cirrhosis-related morbidity and mortality is the development of variceal hemorrhage, a direct consequence of portal hypertension. The reported prevalence of esophageal varices in patients with chronic liver disease varies from 24% to 81% [1][2][3] . Variceal hemorrhage occurs in 25%-40% of patients with cirrhosis, and is associated with a mortality rate of up to 30% [1,2] .…”
Section: Introductionmentioning
confidence: 99%
“…Die TEE ist gut geeignet, die kardiale Funktion zu beurteilen sowie die Volumen-und Pharmakotherapie zu steuern [9,67]. Eine relative Kontraindikation stellen die häufig gestörte Gerinnung und Ösophagusvarizen dar [22,26], die 30-40 % der Patienten mit kompensierter, 80 % mit dekompensierter Leberzirrhose und 73 % der Patienten mit ESLD aufweisen [18,74] …”
Section: » Klassisches Monitoring Durch Intraoperative Tee Sinnvoll Eunclassified